Formation and function of sperm tail structures in association with sperm motility defects - Lehti, Mari S.; Sironen, Anu (My University, 2017)
Male infertility is an increasing problem partly due to inherited genetic variations. Mutations in genes involved in formation of the sperm tail cause motility defects and thus male infertility. Therefore it is crucial to understand the protein networks required for sperm differentiation. Sperm motility is produced through activation of the sperm flagellum, which core structure, the axoneme, resembles motile cilia. In addition to this cytoskeletal axonemal structure sperm tail motility requires various accessory structures. These structures are important for the integrity of the long tail, sperm capacitation and generation of energy during sperm passage to fertilize the oocyte. This review discusses the current knowledge of mechanisms required for formation of the sperm tail structures and their effect on fertility. The recent research based on animal models and genetic variants in relation to sperm tail formation and function provides insights into the events leading to fertile sperm production. Here we compile a view of proteins involved in sperm tail development and summarize the current knowledge of factors contributing to reduced sperm motility, asthenozoospermia, underline the mechanisms which require further research and discuss related clinical aspects on human male infertility.
Keywords: Sperm; motility; male infertility; spermatogenesis; sperma